(untitled) (American Journal of Islam and Society, 1992)
Three great regions of America deserve a Muslim’s attedon because of their Islamic past: Brazil in South America; the Caribbean, which scarcely has been explored in this tespect; and the United States. Over 12 percent of the United States’ population, and even more in the Caribbean, is of African origin, whereas Brazil has a similar or greater proportion of African descent. The enslavement and transportation of Africans to the New World continued for another three or four centuries after the region’s indigenous Indian populations had either been killed off or driven into the plains and wooc1s. While knowledge of the original African Muslims in Notth America is vague ly acknowledged, teseatch is still required on the West Indies. Brazil’s case, however, is clearer due to its proud history of the Palmares republic, which almost achieved its freedom in the seventeenth century, and the clearly Islamic nineteenth-century Male movement. As a postscript, the Canudos move ment in 1897 also contained some Islamic features. In the Spanish colonies, the decline of the indigenous Indian populations began quickly. To offset this development, Bartolome de Las Casas (1474- 1566), Bishop of Chiapas, Mexico, suggested the importation of enslaved Africans to the new colonies, whete they could then be converted to Christianity. Few persons have exercised such a baneful effect on society as this man, who is often called the "Apostle of the Indies." However, othes knew him as the "Enslaver of Africans," especially the Muslims, who he called "Moots." These facts of African slavery apply to almost all of the Atlantic coast of the Americas, from Maryland and Virginia to Argentina, as well as to some countries along the Pacific coast such as Ecuador and Peru. If this aspect of Muslim history and the Islamic heritage is to be preserved for human history, we need to devote more study to it. This tragedy began in the sixteenth century and, after mote than four hundred years, its effects are still apparent. If those Africans caught and sold into slavery were educated, as many of them were, they were generally Muslims and wrote in Arabic. Thus, many educated and literate slaves kept the records for their sometimes illiterate plantation masters, who often could not read or make any mathematical calculations, let alone handle formal bookkeeping. In 1532, the first permanent European settlement was established in Brazil, a country which since that date has never been wholly cut off from West Africa: even today trade is carried on with the Guinea coast. Yoruba influence from Nigeria and Benin has been almost as pervasive in some regions of ...